Computer simulation modeling of Leaf Area Index (LAI) in maize - Bakó, Károly; Huzsvai, László (Acta Agraria Debreceniensis, 2014)
This study presents a PHP-based model capable of calculating maize leaf area index. The model calculates LAI from emergence to 75% silking. The basis of calculation is represented by the daily average temperature values. The usability of the model was tested using three years' temperature and LAI data series from the values obtained by the weather station set up at the Látókép Experiment Site of the University of Debrecen, Centre for Agricultural Sciences between 1994 and 1996. During the running of the model, it was observed that temperature affects the intensity of leaf development to a various extent.